Kekuatan Unsur Intrinsik Cerpen Dalam Kumpulan Cerpen - Catur Feri; Doni Putra (Arsil Media, 2023)
As stated by Adorno and Lyotard, postmodernism makes humans lose their cultural sides and even their humanity. This could be due to influences from the outside world that influence mindsets due to access to information, human dependence on tools or technology, and strengthening individual awareness. On the other hand, as argued by Adorno, the continued reach of advanced capitalism, making them a market, brings about the death of consciousness. Meanwhile, Lyotard refers to a phase of inhumanism in which humans will lose their humanity because of their dependence on techno-science, Sim (2003: 8).